Treinamento de velocidade na tarefa de reconhecimento de símbolos presentes na notação musical a partir do uso de discriminação condicional - Henrique de Almeida Galvão (2022)
Music notation reading is a complex activity that requires different skills and must be executed in a rapid manner. One of these skills – the recognition of notes pitch in the music score – has been taught successfully by behavior analysis experimental studies. However, little has been investigated about the speed of response acquired by individuals in such experiments. The current study elaborated and investigated a computer Training Program involving two interventions: a conditional discrimination training, used to teach symbolics relations that are essential in music notation reading; and a velocity training, that had the intention to reduce the time spend to recognize the symbols learned. The stimuli used were: seven written musical notes (A) and seven musical notes drawn in the pentagram (Treble clef). In addition, the study sought to compare the speed acquired in the experiment, with experts’ average speed in the task of recognizing pitch in a music score. Participants were 13 volunteers with different levels of familiarity with the target task: three of them were part of the Expertise Group and performed only the Pre-Test of the Training Program; ten of them were in the Expertise-less Group and performed the whole Training Program, a Generalization Test, and a Follow-up procedure (14 days). The results indicate that the Program was able to teach the symbolic relations and improve the participant’s recognition time. There were symbols generalizations to the context of a sheet music for half notes and quarter notes. However, there were no generalization for whole notes, neither the eighth notes, pointing out the need to include different symbol in the Training Program. In the follow-up procedure, many participants maintained their accuracy percentage (the average score was around 84%), demonstrating that they still remembered what was learned previously. The speed, however, dropped for all participants due to lack of training. After performing the velocity training once more, there was improvement in speed, with 90% of the participants reaching values above the ones obtained in the first day of experiment. Two of them were able to reach the Expertise Group average in the first day, and six of them in the second day (follow-up). Although the Training Program presented potential contribution to the process of music teaching, other studies are needed to investigate the amplitude of the results found in this study, such as: the consistency of the results outside of the computerized practice, the possibility to teach different symbols, and the integration of note recognition with different tasks involved in music notation reading.